Analisis Efek Inflasi, Suku Bunga, Ekspor dan Nilai Tukar Terhadap Pertumbuhan Ekonomi Indonesia - Ulinuha Alfiolah; Meliza (Universitas Muhammadiyah Surabaya, 2025)
This study aims to examine the impact of inflation, interest rates, exports, and exchange rates on economic growth in Indonesia. The variables in this study include inflation, interest rates, exports, and exchange rates as independent variables, and economic growth as the dependent variable. The method used is a quantitative approach with data processing techniques employing multiple linear regression through the Eviews 13 program, using time series data from 2013 to 2024 in quarterly form. Multiple regression analysis is applied as the analytical technique. Based on the conducted study, the findings partially indicate that inflation and interest rates have a significant negative effect on economic growth in Indonesia, while exports and exchange rates have a significant positive effect on economic growth in Indonesia.